Towards 21st century stellar models: Star clusters, supercomputing and asteroseismology. Issue 8 (30th September 2016) - Campbell, S. W.; Constantino, T. N.; D'Orazi, V.; Meakin, C.; Stello, D.; Christensen‐Dalsgaard, J.; Kuehn, C.; De Silva, G. M.; Arnett, W. D.; Lattanzio, J. C.; MacLean, B. T.
Abstract: Stellar models provide a vital basis for many aspects of astronomy and astro‐physics. Recent advances in observational astronomy – through asteroseismology, precision photometry, high‐resolution spectroscopy, and large‐scale surveys – are placing stellar models under greater quantitative scrutiny than ever. The model limitations are being exposed and the next generation of stellar models is needed as soon as possible. The current uncertainties in the models propagate to the later phases of stellar evolution, hindering our understanding of stellar populations and chemical evolution. Here we give a brief overview of the evolution, importance, and substantial uncertainties of core helium burning stars in particular and then briefly discuss a range of methods, both theoretical and observational, that we are using to advance the modelling.